Does learning orientation matter for nonprofit organization performance? Empirical evidence from Ghana - Baba, Y. (Leadership and Organization Development Journal, 2015)
Purpose – Many changes taking place in the nonprofit sector have created an environment in which organizational learning could be regarded as representing a high-profile notion with strategic importance for nonprofit organizations (NPOs), but its application in the nonprofit sector has not received adequate research attention. The purpose of this paper is to present an empirical test of the relationship between learning orientation and NPO performance. Design/methodology/approach – Literature on organizational learning is briefly reviewed and a marketing-focussed perspective on learning is adopted. Then drawing from resource-based theory and relationship marketing, a conceptual model is developed that links learning orientation to NPO performance, predicting that noneconomic performance would mediate between learning orientation and economic performance. Using Baron and Kenny’s mediation regression procedure, this prediction is subjected to an empirical test with survey data collected on 118 NPOs operating in Ghana. Findings – The paper finds a general support for the view that noneconomic performance is the primary organizational feature that drives economic performance and that learning orientation is an outgrowth of this characteristic. Originality/value – This study addresses the important question of whether paying attention to their mission helps NPOs acquire critical resources from their funding entities, discussing this issue in the context of organizational learning to respond to RBT scholars’ call for more research that highlight the underlying processes through which strategic resources (such as organizational learning) contribute to the organization’s financial outcomes. © Emerald Group Publishing Limited.
Keywords: Ghana; Learning orientation; Nonprofit organizations; Organizational learning; Organizational performance; Strategic orientation